COMPLEX MDCT POSSIBILITIES IN DIAG-NOSTICS OF SIALOADENITIS IN ADULTS - Козаренко, Т.М.; Логаніхіна, К.Ю.; Синюта, С.Б.; Гурандо, В.Р. (World of Medicine and Biology, 2015)
The study involved 35 patients with sialoadenitis which had the following complaints: xerostomia (19 patients, 54, 3%), painful sensations in the submandibular, parotid areas (27 patients, 77.2%), along with an increase in their size (32 patients, 91.4 %), dysphagia due to irradiation pain (8 patients, 22.9%), local hyperthermia skin over the affected salivary glands (12 patients, 34.3%), low-grade (5 patients, 14.3%) or febrile body temperature (1 patient, 2.9%), a combination of local hyperthermia of the skin and fever (6 patients, 17.2%). Using MDCT was determined differential diagnostic signs of inflammation in the salivary gland and the estimated rate heterogeneity with. Thus, the main signs of acute sialoadenitis MDCT is increasing the size of cancer (32 patients, 91.4%), diffuse accumulation of contrast material (2 patients, 94.3%), the presence of inclusions renthenkontrasnyh - sialolitiv (22 patients, 91.4%) . Signs of inflammation and its complications for values heterogeneity coefficient c (c = c = 10-17 and 18-27, respectively).
Keywords: sialoadenits; multidetector computed tomography; coefficient of heterogeneity